“Bright–English for Beginners” Application as a Learning Media: Taking EFL Teachers’ Perspective: “Bright–English for Beginners” sebagai Media Pembelajaran: Perspektif Guru Bahasa Inggris sebagai Bahasa Asing (EFL) - Zahira Shofa Sihotang; Diah Safithri Armin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mobile-Assisted Language Learning (MALL) has become a transformative tool in English language instruction, especially at the elementary level. Specific Background: The